If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
6*x+x-(4/7) = (5*x)/5+6+9 // - (5*x)/5+6+9
6*x+x-((5*x)/5)-(4/7)-9-6 = 0
6*x+x-x-4/7-9-6 = 0
6*x-109/7 = 0 // + 109/7
6*x = 109/7 // : 6
x = 109/7/6
x = 109/42
x = 109/42
| 5t+7t+2p+4p= | | x-0.09=2.22-0.01x | | 3.6(j+4)=1.4(16+j) | | 6-5[4-(6y-3)]= | | 3x^5y^3/10x^3x20x/12y^4 | | 4=-2(x)(x)+3 | | 10a+8(a-3)=15 | | 4=-2x+3 | | 2x+40-4x=1-7x+4 | | 1205(2w-13)=3(2w-5) | | 2ab*3+3xb*2-5b*4+2b*2= | | csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 |